If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6t + -72 = 7t + -84 Reorder the terms: -72 + 6t = 7t + -84 Reorder the terms: -72 + 6t = -84 + 7t Solving -72 + 6t = -84 + 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. -72 + 6t + -7t = -84 + 7t + -7t Combine like terms: 6t + -7t = -1t -72 + -1t = -84 + 7t + -7t Combine like terms: 7t + -7t = 0 -72 + -1t = -84 + 0 -72 + -1t = -84 Add '72' to each side of the equation. -72 + 72 + -1t = -84 + 72 Combine like terms: -72 + 72 = 0 0 + -1t = -84 + 72 -1t = -84 + 72 Combine like terms: -84 + 72 = -12 -1t = -12 Divide each side by '-1'. t = 12 Simplifying t = 12
| 60-5x=80-13x | | 8n-[4n+5]=3 | | 10b-2(b+3)=56 | | (x+1)(x-2)+2x=(x-3)(x+2) | | -22=7x+22 | | 6x+8+6x=140 | | x^2+0.06x=0.028 | | 5[3x-2]=20 | | w-7=150 | | 4-8x+2=30 | | 7w=150 | | 64-12= | | 7-w=150 | | -10.95+12.48+18.6p=-17.97+16.1p | | -3r+3=-4r+5 | | 3+5y=30+2y | | 20x^4-65x^3-60x^2=0 | | -(1+7)-5(-7-x)=36 | | -8q+18q+10=7q-17 | | 65=6c+11 | | 3a-6(4a+5)=-6a-15 | | 2x-1=12x+121 | | 20z-14=5z+20z+11 | | 6=4+2z | | 6x^3+32x^2-10x=0 | | 2c-10+2=-20c-8 | | 118=1-3(6x-3) | | 19-17g=-8g-14g-6 | | 2p=-3 | | 7+2a=15 | | 19-17g=8g-14g-6 | | 2+4x=-4+x |